Prevalence of psychosocial findings and their correlation with TMD symptoms in an adult population sample - Giorgio Iodice; Ambra Michelotti; Vincenzo D'Antò; Stefano Martina; Rosa Valletta; Roberto Rongo (SpringerOpen, 2024)
Abstract Background and aim Some studies suggested an association between Temporomandibular Disorders (TMD) and psychosocial status, but most of them are focused on samples of patients looking for treatment or present limits of sample representativeness. The aim of the present study was to evaluate the psychosocial status in a large sample of adult population, further than to assess its association to TMD symptoms, oral behaviours, and self-reported facial trauma. Results the study sample included 4299 subjects older than 18 years randomly recruited from general population in public spaces during their daily life (1700 Males, 2599 Females mean ± SD age = 40.4 ± 18.1). Psychosocial status and pain-related disability were assessed by means of Patient Health Questionnaire 4 (PHQ-4) and Graded Chronic Pain Scale (GCPS). TMD symptoms were assessed by RDC/TMD and validated screening tools for TMD pain. Oral Behaviours Checklist was used to investigate on oral behaviours. Logistic regression model was used to evaluate the association of the psychosocial status, TMD symptoms, trauma, and oral behaviours. The association was tested using both univariate and multivariate models. The PHQ4 evaluation showed a severe impairment in 4.6% of our sample, moderate in 18.8% and mild in 32.5%. We found a Characteristic Pain Intensity (CPI) level and Interference Score greater that 30 respectively in 36.2% and 22.2% of the study sample. The GCPS status revealed a high disability with severe limitation in 2.5% of the sample, high disability with moderate limitation in 7.0%, low disability high pain intensity in 7.4% and low disability low pain intensity in 37.8%. Anxiety and depression's levels were significantly associated with gender, TMD pain, coexistence of TMD Pain and sound, and oral behaviours. GCPS status was significantly associated with age, TMD Pain, coexistence of TMD pain and sound, trauma, and oral behaviours. Conclusions In the general population, psychosocial impairment is associated to TMD pain, female gender, and report of oral behaviours. Hence, in adults with TMD accompanied by pain, psychosocial status should also be evaluated.